Emergence of Carbapenem-Resistant blaPOM-1 Harboring Pseudomonas otitidis Isolated from River Water in Ghana - Frederick Ofosu Appiah; Samiratu Mahazu; Isaac Prah; Taira Kawamura; Yusuke Ota; Yohei Nishikawa; Mitsunori Yoshida; Masato Suzuki; Yoshihiko Hoshino; Toshihiko Suzuki; Tomoko Ishino; Anthony Ablordey; et al. (Antibiotics)
Introduction: Pseudomonas otitidis, known for carrying the blaPOM-1 gene and linked to various diseases, is widely distributed. However, its prevalence in Ghana is unknown, mainly due to misidentification or inadequate research. In this study, for the first time, we characterized P. otitidis from Densu river water in Ghana. Methods: The antimicrobial susceptibility and whole genome characteristics of two strains (Tg_9B and BC12) were determined. The resistance and virulence features were determined using ResFinder and the VFDB database, respectively. Maximum-likelihood phylogeny was conducted based on amino acid sequences of blaPOM-1 and P. otitidis core genomes. Results: The strains carried blaPOM-1 on the chromosome, with only Tg_9B showing intermediate resistance to meropenem. Tg_9B had a unique genetic make-up downstream of blaPOM-1, compared with BC12 and other reference strains. Both strains harbored virulence factors able to induce pathogenicity through immune evasion. The efflux pump genes (adeF, rsmA, and qacG) were present in the genomes of all the strains used in this study. The amino acid sequences of POM-1 in the strains shared a sequence homology with seven other sequences from different countries. Conclusions: This study highlights the emergence of blaPOM-1 harboring P. otitidis in Ghana and affirms the conservation of blaPOM-1 and adeF, rsmA, and qacG in the species.